KONTRIBUSI PEMIKIRAN FILSAFAT IQBAL BAGI PENEGAKAN HAK ASASI MANUSIA - Anshori Lidinillah, Mustofa (Al'Adalah, 2022)
Human Rights are considered God's gift given to humans from birth. However, discrimination, harassment, intimidation, repression, and other human rights violations still occur in social life. The article discusses the relevance of the contemporary Muslim thinker Muhammad Iqbal to progressive humanitarian ideas, especially in contemporary human rights discourses. This interdisciplinary research comprehensively analyzes Iqbal's thoughts within the framework that Islamic values and human rights principles do not contradict or reinforce one another. Iqbal is known as a humanist, religious and universal intellectual. In the religious context, Iqbal's thoughts refer to Islamic teachings, emphasizing the self-affirmation of human existence, that human nature as a divine being and a righteous believer should uphold human rights in social life.